Psychological intervention based on psychoneuroimmunology improves clinical evolution, quality of life, and immunity of children with leukemia: A preliminary study. Issue 1 (March 2019) - Chacin-Fernández, Josymar; Chacin Fuenmayor, Margarita; Piñerua-Shuhaibar, Lorena; Suarez-Roca, Heberto
We conducted a non-randomized, open-label clinical trial to assess whether a psychoneuroimmunology-based intervention enhanced immunity in children with acute lymphoblastic leukemia undergoing chemotherapy. In total, 16 children (44% female) received psychoneuroimmunology-based intervention, whereas 12 (50% female) received health psychoeducation (controls). The primary outcome was immunity markers, being clinical conditions the secondary outcome. Psychoneuroimmunology-based intervention increased immune markers (CD8+ T, B, and natural killer cells, serum immunoglobulin A, and immunoglobulin M) and quality of life, whereas it shortens the duration of fever and use of antipyretics, antibiotics, analgesics, and respiratory therapy. Immunity markers correlated with clinical conditions. Thus, psychoneuroimmunology-based intervention could reduce hospital cost and increase patient well-being.